Music education and the challenge of democratization in the “school plant” - Oliveira, Wenderson Silva; Borges, Eduardo Henrique Narciso (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2017)
The Law 13.278/2016 (BRAZIL, 2016) made the teaching of Visual Arts, Dance, Music and Theater compulsory in the curriculum of basic education throughout the country. However, specifically regarding Music teaching, there are a number of factors and problems that hinder the full insertion of the discipline in Brazilian schools, ranging from the lack of material resources to the social legitimacy of the discipline and the valuation of this knowledge as something Significant for the formation of students. In this sense, this article proposes to analyze the social and political dynamics that permeate the teaching/learning music, as well as the experiences in collective teaching of musical instruments in the attempt of democratization of Music teaching aiming at social inclusion through it. Likewise, it opens the possibility of promoting a paradigm shift and expansion of the student horizons in relation to artistic and cultural knowledge, encouraging the creativity and the capacity for interpretations and diverse readings of the world around them.